Embedding Nationalist Values in History Education Through Early Human Cohabitation in Java Caves - Dimas Anggoro; Sulistyo, Wahyu Djoko (Universitas Negeri Semarang, 2025)
This study investigates the presence of nationalist values within the narrative of early human cohabitation in cave shelters in Java, positioning it as a potential educational resource. The objective of this research is to examine how interactions between distinct racial groups, specifically Australomelanesoid and Mongoloid populations can be utilized to foster students’ nationalist consciousness. Employing a qualitative literature review approach, the study seeks to identify the embedded nationalist values in the inter-racial coexistence of prehistoric human communities in Java and assess their potential as learning materials to reinforce national identity among students. The findings of this research suggest implications for educational practice, advocating for the integration of prehistoric cohabitation narratives into the curriculum as a means to cultivate a deeper understanding of national identity and promote social cohesion among learners.